Fullerene derivatives as nano-additives in polymer composites. (July 2017) - Penkova, Anastasia V.; Acquah, Steve F. A.; Piotrovskiy, Levon B.; Markelov, Denis A.; Semisalova, Anna S.; Kroto, Harold W.
Abstract : Since their discovery, fullerenes have become one of the most recognizable molecules in science. The 'beautiful molecule' described by Harold W.Kroto has been subtly referenced in movie, and has adorned the covers of many science-based textbooks. The physical and chemical properties of fullerenes have generated a lot of interest in the science community with many opportunities to develop new avenues for scientific research. Difficulties in the commercial use of fullerenes ( e.g ., C60 ) have likely been due to issues with solubility. Fortunately, the situation has improved over the last decade with research into fullerene derivatives. Once modified, fullerenes may have applications in a variety of areas including medicine, drug delivery, optoelectronics and electrochemistry. The addition of low concentrations of carbon nanoparticles to polymer matrices may result in significant changes in the function of polymer-based composite materials. This review will highlight the applications of fullerene derivatives as nano-additives for polymer composites. Various fullerene derivatives, viz ., water-soluble carbon nanoclusters modified with hydroxyl and carboxyl groups, as well as hydrophobic fullerenes (metallofullerenes and methanofullerenes) will be evaluated in regard to their potential impact on commercial applications, in particular, photovoltaic devices, fuel cells, membrane technology and biocompatible electroactive actuators. We, members of Harold W Kroto's research group in Florida and international collaborators, miss his exuberance and passion for engaging with young researchers, and we stand committed to preserving his legacy of science and outreach. The bibliography includes 387 references.